Decision to Adopt the Academic Program (Global Journal of Management and Business Research, 2011)
The purpose of this study was to examine attitudes of the students toward adoption of the academic program. A 19-item questionnaire was adapted to collect data on the decision by the students. This study is based on primary data, which collected from 154 students from 4 different University of Lahore District, Pakistan. For this purpose self designed questionnaire was used for data collection.. Cranach-Alpha reliability is 78% and 95 % students done matriculation in science subjects. Majority of students decided their graduation degree himself. 77% students decided about their professional degree themselves. 20.3 % students feel undue pressure from their parents to undertake academic related decision. 80.5% students out of 20.3% feels that pressure of their parents are in their favor and 19.5% feels that the pressure was not in their favor and they feel that if they were given freedom to select their academic decision, they would be at better place in their life and concluded that positive impact of decision making on academic achievement. After thorough analysis it concluded that mostly students take their academic decision themselves and females have less decision making power as compare to male because Pakistan being as a Muslim Country doesn't given freedom to females to make decision regarding any issue of their life.
Keywords: Decision making; students; university; academic program; education and Pakistan